The importance of information and communication technology as mechanism for legal education, practice and dispute resolution in Nigeria (2016)
Information and Communication Technology (ICT) is a set of activities facilitated by electronic means for the purpose of processing, transmitting and displaying information. Some of its components include hardware, software and telecommunication equipment. It is widely believed that the present time is information age and the near daily advancement in ICT have revolutionised the traditional or customary way of doing things. ICT can now be applied to virtually every field of human endeavour of which law is not an exception. At present, the changes brought about by the use of ICT can be seen in legal education, research and practice. For instance, students, researchers, lecturers, practitioners and judges can in the comfort of their homes and offices access millions of materials online including laws and judicial decisions of Nigeria and other jurisdictions. The aim of this paper is to examine the ways by which ICT can and has transformed the traditional and customary methods of doing things including law in Nigeria. The specific objective of this paper is to analyse the impact of ICT on Nigeria legal education, legal practice, legal research as well as online transaction and dispute resolution. The paper highlights various challenges confronting the prospects of ICT in Nigeria. The paper concludes with recommendations.